Associations of Dietary Salt and Its Sources with Hemoglobin A1c in Patients with Type 2 Diabetes Not Taking Anti-Diabetic Medications: Analysis Based on 6-Month Intervention with a Moderate Low-Carbohydrate Diet - Haimoto H (Dove Medical Press, 2021)
Hajime Haimoto,1 Takashi Murase,2 Shiho Watanabe,3 Keiko Maeda,4 Kenji Wakai5 1Department of Internal Medicine, Haimoto Clinic, Kasugai City, Aichi, Japan; 2Division of Endocrinology and Diabetes, Libra Sasashima Medical Clinic, Nagoya City, Aichi, Japan; 3Division of Clinical Nutrition, Haimoto Clinic, Kasugai City, Aichi, Japan; 4Department of Health and Nutritional Sciences, Faculty of Health and Sciences, Aichi Shukutoku University, Nagakute City, Aichi, Japan; 5Department of Preventive Medicine, Nagoya University Graduate School of Medicine, Nagoya City, Aichi, JapanCorrespondence: Hajime HaimotoDepartment of Internal Medicine, Haimoto Clinic, Kasugai City, Aichi, JapanTel +81-568-85-8226Fax +81-568-85-8315Email haimoto@gol.comObjective: Based on biological studies, the hyperglycemic effect mediated by sodium-glucose co-transporter 1 in the intestine is stronger for foods containing more sodium chloride. Observational studies have demonstrated that type 2 diabetes (T2DM) incidence increases as salt intake increases. We aimed to elucidate associations of total salt and its sources with hemoglobin A1c (HbA1c) in patients with T2DM.Methods: We conducted an observational study using data from a 6-month moderate low-carbohydrate dietary intervention in 245 outpatients with T2DM (138 men) without antidiabetic medication. Intakes of total salt and its sources, carbohydrate and total energy were assessed at baseline and 6 months based on 3-day dietary records. Multiple regression analyses were performed to examine associations of Δtotal salt or its sources with ΔHbA1c.Results: Salt intake significantly decreased in men (change: − 0.92 ± 3.53 g/day) but not in women (0.11 ± 2.28). HbA1c (men: − 1.5 ± 1.6%; women: − 0.9 ± 1.3%), carbohydrate (men: − 115 ± 104 g/day; women: − 64 ± 71) and total energy (men: − 439 ± 660 kcal/day; women: − 192 ± 438) significantly decreased in both sexes. Multiple regression analysis revealed that reducing intakes of total salt and salt from salty snacks, meat processed foods, Chinese noodles with soup and table salt by 1.0 g was associated with decreases in HbA1c of 0.11% 1.18% 0.47% 0.38% and 0.26%, respectively, in men, while reducing salt from miso by 1.0 g was associated with a decrease in HbA1c of 0.30% in women. The associations were dependent on Δcarbohydrate or Δtotal energy in men, while the association of Δsalt from miso in women was independent of them.Conclusion: Reducing total salt and its sources had differential associations with HbA1c. Individual associations depended on Δcarbohydrate or Δtotal energy in men, while that of salt from miso in women was independent of them.Keywords: salt intake, dietary sodium, salt sources, carbohydrate intake, hemoglobin A1c, low-carbohydrate diet